A ‘White Lie’ of Business Informality: An Exploration of Non-Registered White-owned Businesses in the United States of America - Pisani, Michael J. (Journal of Economic Analysis, 2023)
Utilizing a 2021 nationally representative sample of 7,504 White-owned employer businesses (WOBs) in the United States of America (USA), the extent, and the determinants of WOB business registration are estimated. Business registration is employed as a proxy for business in/formality. Approximately one-fifth (22.5%) of all employer WOBs are unregistered or informal business concerns hidden from government purview. The primary determinants of employer WOB informality are business size (annual revenues under $500,000 and few paid employees), a business owner with less than a four-year college degree, and an upbringing in a lower- or middle-class environment, among other findings. Notably, this research reveals the white lie of the magnitude of White-owned employer business informality in the USA.